Chapter As in trans art - Hayward, Eva (Amsterdam University Press, 2023)
This article engages with trans artistic practices: both trans in art as well as trans as art. It takes as its point of departure the artistic work of Ro Robertson, Tama Sharman, and Erica Rutherford, each of whom works with trans in different ways. In our analysis, we take a cue from Rosemarie Buikema's attunement to the materiality and medium specificity of artworks, and we discuss how these elements offer new entry points into a consideration of transness.